Using isozyme polymorphism to assess genetic variation within cultivated yams (Dioscorea cayenensis/Dioscorea rotundata complex) of the Republic of Benin - Dansi, A.; Mignouna, H.; Zoundjihékpon, J.; Sangare, A.; Asiedu, Robert; Ahoussou, N. (2000)
Four hundred and sixty-seven accessions of cultivated Guinea yam (Dioscorea cayenensis/Dioscorea rotundatacomplex) collected from different localities of Benin Republic were analysed to study isoenzymatic variability in seven enzyme systems: aspartate aminotransferase (AAT), esterase (EST), glucose-6-phosphate dehydrogenase (G6PDH), isocitrate dehydrogenase (IDH), phosphoglucomutase (PGM), phosphoglucoisomerase (PGI), and shikimate dehydrogenase (SKDH) using starch gel electrophoresis. Polymorphism was observed in all of the enzyme systems and a total of 62 electromorphs of different frequency and variability patterns were recorded. Different combinations of banding patterns of these systems led to identification of 227 different cultivars within the 467 accessions analysed. For an old and vegetatively propagated crop (with a considerable number of vernacular names) such as yam, and for which a high rate of duplication is expected, the 227 cultivars were found to be good enough to be considered as the adequate number of accessions representing the diversity in the germplasm analysed. Cluster analysis (UPGMA) produced a most likely division of the 467 accessions into two groups corresponding to D. rotundata Poir. and D. cayenensis Lam., supporting the concept that the two forms of guinea yam represent different genetic entities. The different clusters formed within the white yams (D. rotundata) did not exactly conform to the known cultivar groups. Additional polymorphic enzymes are needed for an accurate isozyme-based genetic discrimination of most of the cultivar groups.